The Impact of Health Technology Use on Digital Literacy Among Communities: An Empirical Study in Tanzania - Shagembe, Magolanga; Issa, Rand Sayed; Azlifa, Mariyam (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This This study investigates the relationship between health technology use and digital literacy skills in the general community, particularly in the context of Tanzania, where the adoption of digital health tools is gaining momentum. The rapid integration of information technology (IT) in health services—such as telemedicine, e-health records, and mobile health applications—has made digital literacy an essential skill for individuals to access and utilize these technologies effectively. Methodology: Through a mixed-methods approach, this study gathered data from 220 respondents from Tanzania, exploring their digital literacy levels and attitudes toward health technology. Main Findings: The results revealed that 58.6% of respondents had a positive view of health technology, with 62.3% demonstrating strong digital literacy skills. A regression analysis identified a significant positive relationship between health technology use and digital literacy, explaining 65.1% of the variance in digital literacy skills (R² = 0.651). Qualitative interviews provided deeper insights, highlighting barriers faced by older adults and individuals with lower educational backgrounds, particularly in accessing and utilizing digital health services. Novelty/Originality of this study: This study contributes to the growing body of knowledge on the intersection of health technology adoption and digital literacy by emphasizing the socio-demographic disparities in access. It calls for targeted digital literacy training as an integral part of public health programs, ensuring that all demographic groups, particularly vulnerable populations, can fully benefit from digital health innovations. The study also proposes policy interventions to bridge the digital divide and improve equity in healthcare access